Kultura strachu - Puppel, Stanisław; Puppel, Joanna (Scripta Neophilologica Posnaniensia, 2021)
The ‘culture of fear’ constitutes an important environment for mankind. It is an interplay of biological, socio-cultural and linguistic dimensions which, in fact, underlie human existence. The dominance of one subtype of culture with respect to fear, the dystopian culture, pulls mankind into a culture of aggression, competitiveness and intolerance (or into the win-lose perspective). On the other hand, eutopian culture pulls mankind into a culture of non-aggression, cooperation, tolerance and inclusiveness (or into the win-win perspective). In fact, one may easily envisage that a well-functioning human society should remain in a state of balance between the two types of culture and it is the dystopian type of culture that should be kept in check, while the eutopian culture should be favoured if the earth as the carrier of all life, the existing biodiversity, and humanity, are to be sustained.